2015
DOI: 10.1016/j.jagp.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Computerized and Virtual Reality Cognitive Training for Individuals at High Risk of Cognitive Decline: Systematic Review of the Literature

Abstract: The aim of this study was to assess the efficacy of cognitive training, specifically computerized cognitive training (CCT) and virtual reality cognitive training (VRCT), programs for individuals living with mild cognitive impairment (MCI) or dementia and therefore at high risk of cognitive decline. After searching a range of academic databases (CINHAL, PSYCinfo, and Web of Science), the studies evaluated (N = 16) were categorized as CCT (N = 10), VRCT (N = 3), and multimodal interventions (N = 3). Effect sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
143
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(175 citation statements)
references
References 73 publications
20
143
0
5
Order By: Relevance
“…More recently, a systematic review of the literature (Coyle et al, 2015) focused on computerized cognitive training (CCT) and virtual reality cognitive training (VRCT) for individuals at high risk of cognitive decline. The studies evaluated (N = 16) were categorized as CCT (N = 10), VRCT (N = 3), and multimodal interventions (N = 3).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a systematic review of the literature (Coyle et al, 2015) focused on computerized cognitive training (CCT) and virtual reality cognitive training (VRCT) for individuals at high risk of cognitive decline. The studies evaluated (N = 16) were categorized as CCT (N = 10), VRCT (N = 3), and multimodal interventions (N = 3).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, some studies have demonstrated that cognitive improvement does not transfer easily to the realisation of new tasks and that these yield better results when established in a repetitive and increasing manner (difficulty levels) [24]. Similarly, other studies have shown that cognitive stimulation interventions can be administered not only through therapist instruction, but also through computerized technology [25][26] Over the last years, interest has thus been focused on interventions specially based on computerized cognitive stimulation or technologically-assisted cognitive stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies have shown that cognitive stimulation interventions can be administered not only through therapist instruction, but also through computerized technology [25][26] Over the last years, interest has thus been focused on interventions specially based on computerized cognitive stimulation or technologically-assisted cognitive stimulation. In terms of cognitive impact, this is clearly justified due to the fact that ICT-supported interventions can have a positive impact on attention measures, executive functions and memory [11,17,[20][21][22][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing and strengthening research activities related to VR platforms offers the possibility of more clearly ascertaining the potential efficacy of this technology as a useful tool for cognitive interventions in ADRD, including cognitive training (CT). A deeper knowledge and experience in this field is needed to allow the application of novel concepts, approaches, and methods to the treatment of dementia (Robert, Leroi, & Manera, 2016 Rather, most have used conventional graphic workstations to create non-immersive scenarios (Anguera et al, 2013b;BartolomĂ©, Zapirain, & Zorrilla, 2012;Burdea et al, 2013;Chapoulie & Guerchouche, 2014;Coyle, Traynor, & Solowij, 2015;Lee et al, 2014;Tarnanas et al, 2013;Tarnanas, Tsolaki, Nef, MĂŒri, & Mosimann, 2014;Tu et al, 2015).…”
Section: The Role Of Ict Emerging Applicationsmentioning
confidence: 99%
“…VR, a recent branch of ICT, has been suggested for use in some areas of neuropsychology (Coyle, Traynor, & Solowij, 2015 Emerging VR applications today address the challenge of diagnosis and cognitive training of MCI and ADRD patients, concentrating on navigation and orientation, face recognition, cognitive functionality, and other Instrumental IADL (Jekel et al, 2015). VR exposes cognitively impaired patients to computer-generated VEs providing a sensation of "presence" or "being there," for the patient to interact with in a multisensory fashion through quasi-naturalistic real-life-like stimuli.…”
Section: Virtual Reality In Neuropsychologymentioning
confidence: 99%